European Journal of Transport and Infrastructure Research 2015
DOI: 10.18757/ejtir.2015.15.4.3103
|View full text |Cite
|
Sign up to set email alerts
|

Detecting activity type from GPS traces using spatial and temporal information

Abstract: Detecting activity types from GPS traces has been important topic in travel surveys. Compared to inferring transport mode, existing methods are still relatively inaccurate in detecting activity types due to the simplicity of their assumptions and/or lack of background information. To reduce this gap, this paper reports the results of an endeavour to infer activity type by incorporating both spatial information and aggregated temporal information. Three machine learning algorithms, Bayesian belief network, deci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…This authenticates an enhanced concentration amongst current and future researchers into all four main focused areas, especially detection. Feng and Timmermans (2015), used learning algorithms, Bayesian belief network, DT and random forest to detect activity types from GPS traces. Carbonneau et al (2008) concluded in their research that the neural network and support vector machines show the best…”
Section: Main Area Of Focus and Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…This authenticates an enhanced concentration amongst current and future researchers into all four main focused areas, especially detection. Feng and Timmermans (2015), used learning algorithms, Bayesian belief network, DT and random forest to detect activity types from GPS traces. Carbonneau et al (2008) concluded in their research that the neural network and support vector machines show the best…”
Section: Main Area Of Focus and Techniquesmentioning
confidence: 99%
“…However, there is as yet no highlight on which ML techniques or models should be best adopted to undertake anomaly detection in the field of LSCM. One of the few papers with a focus on detection was conducted by Feng and Timmermans (2015) which was written about the incorporation of three ML algorithms, namely Bayesian belief network,decision tree and random forest to detect activity types from GPS traces. The difference in main areas of focus resembles the imbalance in the popularity of the exploited ML techniques.…”
Section: The Need For Balanced Attentionmentioning
confidence: 99%